Development of Future Skills Assessment Criteria for Undergraduate Students in Cambodia: Mixed Methods Research - Boun, Kakada; Makmee, Pattrawadee; Wongupparaj, Peera (The Journal of Behavioral Science, 2024)
Background and Problem: Cambodian students face challenges due to a lack of essential skills for future job demands, which stems from limited access to modern educational resources and a mismatch between current curricula and evolving global skill requirements. However, research studies on this issue remain limited. Objective/ purpose: This study aims to: 1) analyze and validate a future skills model using multilevel confirmatory factor analysis (MCFA); and 2) develop future skills assessment criteria for Cambodian undergraduate students. Design and Methodology: A mixed-method multilevel explanatory sequential design was employed in two phases. Quantitative data were collected from 400 Cambodian students across 50 majors using multistage random sampling. Qualitative data were gathered through in-depth interviews with seven key informants. Data analysis involved MCFA for quantitative data and content analysis for qualitative data. Results: The MCFA revealed three main components of future skills: learning and innovation skills, information, media and technology skills, and life and career skills ( = 83.96, df = 78, RMSEA= .01, CFI = 1.00, TLI = .98, SRMRW = .02, SRMRB = .08). At both the student and major levels, life and career skills emerged as the most significant factor, which aligns with key informants' opinions. The study developed 86 indicators and 102 assessment criteria across three main components, based on both quantitative and qualitative data. Conclusion and Implications: The study's results can be used as guidelines to improve curricula, teaching methods, and assessments of future skills for undergraduate students, helping them to be well prepared for their future careers. Originality/Value for the Sustainable Development Goals (SDGs): This research on future skills and assessment criteria illuminates competencies needed for rapid technological and social changes. It informs educational interventions promoting lifelong learning and workforce readiness. By integrating critical skills into curricula, the study aligns with future workforce demands, contributing to SDG-4 (quality education) and SDG-8 (decent work and economic growth). The resulting framework guides educators and policymakers in bridging the gap between academic preparation and evolving workforce needs in Cambodia, equipping undergraduates for 21st century workplace challenges.